Disruption of the blood–brain barrier contributes to neurobehavioral changes observed in rheumatic heart disease - Rukshan Ahamed Mohamed Rafeek; Riya Thapa; Samarjeet Saluja; Bipandeep Banga; David McMillan; Kadaba Sri Sriprakash; Nicholas M. Andronicos; Adam Hamlin; Natkunam Ketheesan (Animal Models and Experimental Medicine, 2025)
Abstract Sydenham chorea (SC) is the neurological manifestation associated with acute rheumatic fever (ARF). ARF and rheumatic heart disease (RHD) are autoimmune complications triggered by a group A streptococcal (GAS) infection. In ARF/RHD and SC, tissue cross‐reactive antibodies and T‐cells generated against GAS antigens have been implicated in the pathogenesis. In SC, antibodies against GAS antigens are known to cross‐react with neuronal proteins causing neurological manifestations including choreiform movements and neuropsychiatric symptoms such as irritability, attention deficit, and obsessive‐compulsive disorder. Previous studies in a rat autoimmune valvulitis (RAV) model of RHD, have shown that injection of streptococcal M protein could cause both cardiac and neurological symptoms. In this study it was shown that adoptive transfer of serum with anti‐GAS M antibodies to naive rats caused carditis but failed to demonstrate neurobehavioral symptoms. However, when the blood–brain barrier (BBB) was disrupted using lipopolysaccharide, all animals that received anti‐GAS M protein antibodies, developed neurobehavioral defects in addition to carditis. This highlights that impaired BBB integrity is essential for the development of neurobehavioral symptoms. The use of the RAV model and the disruption of BBB required for the development of neurobehavioral changes provides a platform to further investigate the mechanisms that lead to antibodies binding to basal ganglia structures that cause SC.